Kajian Konseptual tentang Integrasi Media Visual dalam Pembelajaran Kosakata Bahasa Arab - Anwar Abd. Rahman; Nurfadillah Nurfadillah; Fathimah Azzahra Ilyas; Sitti Fatima; Nurul Atira Muqmin; Fausiah Fausiah (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study aims to conceptually examine the role of visual media in Arabic vocabulary learning and its relevance in the context of education in the digital era. Vocabulary mastery is a fundamental component in learning Arabic; however, in practice, vocabulary learning often encounters various challenges, such as the abstract nature of vocabulary, low student motivation, and the dominance of conventional teaching methods. This study employed a qualitative approach using library research. Data were obtained through a review of relevant scholarly sources, including books, journal articles, and previous research related to visual media and Arabic language learning. Data were collected through documentation techniques and analyzed using content analysis to examine the concepts, roles, and effectiveness of visual media in Arabic vocabulary instruction. The findings indicate that visual media, both conventional and digital, play a significant role in improving vocabulary comprehension, strengthening memory retention, and increasing students’ motivation and engagement in the learning process. Visual media also help transform abstract vocabulary into more concrete and contextual representations, making learning more meaningful and effective. Nevertheless, the implementation of visual media still faces several challenges, including limited facilities, teachers’ digital competence, and the suboptimal use of technology in learning activities. Therefore, it is necessary to develop innovative instructional strategies and enhance teachers’ competencies to ensure that visual media can be utilized effectively and sustainably in Arabic language learning.